2020
DOI: 10.3389/fphys.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autophagy on Chronic Intermittent Hypobaric Hypoxia Ameliorating Liver Damage in Metabolic Syndrome Rats

Abstract: Aim: Our previous study demonstrated that chronic intermittent hypobaric hypoxia (CIHH) can confer hepatic protection by reducing endoplasmic reticulum stress (ERS) in high-fat-high-fructose induced metabolic syndrome (MS) rats. It is known that there is a functional coupling between autophagy and ERS. This study aimed to investigate the effect of CIHH on autophagy function and adenosine mono-phosphate-activated protein kinase-mammalian target of rapamycin (AMPKα-mTOR) signaling pathway in hepatic tissue of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Autophagy is an intracellular catabolic process that allows the degradation of damaged proteins and organelles in lysosomes. Autophagy consists of three major steps: autophagosome formation, fusion with the lysosome, and finally degradation [17]. It was reported by Khambu et al that impaired autophagy decreases the clearance of excessive lipid droplets in hepatocytes that led to the development of non-alcoholic fatty liver (NAFLD) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an intracellular catabolic process that allows the degradation of damaged proteins and organelles in lysosomes. Autophagy consists of three major steps: autophagosome formation, fusion with the lysosome, and finally degradation [17]. It was reported by Khambu et al that impaired autophagy decreases the clearance of excessive lipid droplets in hepatocytes that led to the development of non-alcoholic fatty liver (NAFLD) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al described lower protein levels of Atg7, Beclin 1 (Atg6), LC3, Atg5, and elevated p62 in the livers of obese mice (Yang et al, 2010). Concerning other metabolic disorders, in rats with MetS increased hepatic autophagy activity manifested by elevated LC3-II/I, Beclin-1, mammalian target of rapamycin (mTOR), and p62 autophagy-related proteins, as well as phosphorylated adenosine 5 -monophosphate-activated protein kinase (AMPK) down-regulation, has been reported (Cui et al, 2020). These results appear to reflect an opposite role for autophagy in obesity and MetS, however, they must be carefully analyzed.…”
Section: Metabolic Syndrome and Associated Disordersmentioning
confidence: 99%
“…On the other hand, although there have been multiple versions of consensus within the autophagy community on the use and interpretation of assays for monitoring autophagy (Klionsky et al, 2021), it is notorious that incompliance of investigations to the established guidelines led to a discrepancy in experimental results in hepatic autophagy in the setting of metabolic diseases. For example, while various publications indicate hepatic autophagy enhancement based on results showing high levels of LC3II or Beclin-1, other investigations interpret that the reduction in levels of these parameters means an increase in autophagic activity (Parafati et al, 2015;Gong et al, 2016;Shao et al, 2018;Cui et al, 2020). Therefore, to explain controversies of existing results on hepatic autophagy in obesity, MetS, insulin resistance, NAFLD, or diabetes, it is necessary to adhere to the existing consensus on autophagy parameters, which would permit to have the most appropriate autophagy mediators in the liver to indicate with greater certainty an increase in the formation of autophagosomes and if lysosomal degradation is being carried out properly.…”
Section: Future Directions From the Role Of Hepatic Autophagy In Metabolic Liver Diseasesmentioning
confidence: 99%
“…Current studies have shown the existence of multiple bene ts of CIHH to the organism. For example, CIHH ameliorates renal injury in rats with diabetic nephropathy by activating the HIF1-α signaling pathway [10]; intermittent hypobaric hypoxia enhances HIF stability by inhibiting prolyl hydroxylase (PHD) activity, which activates key adaptive genes to attenuate hypoxic injury in the body [11] CIHH also has the ability to improve hypertension [12,13], improve left ventricular remodeling and myocardial brosis [14],anti-arrhythmia [15,16], attenuate oxidative stress [17], alter cardiac energy metabolism [18], reduce the size of myocardial infarction [19], inhibit in ammatory response and apoptosis [20], improve insulin resistance [13], attenuate endoplasmic reticulum stress [21].…”
Section: Introductionmentioning
confidence: 99%